Cooperation against customs fraud in the European Union - García Guerrero, David (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Customs fraud constitutes a concern for the European Union because it leads to a decrease in community revenue, thereby having a negative impact on its expenditure capacity, since Paragraph 1 of Article 310 of the Treaty on the Functioning of the European Union (TFEU) states that there must be a balance between income and expenditure. It is for this reason that the European Union is continuously developing mechanisms to combat customs fraud, either by keeping those that have worked or by creating new ones.